School Bullying from a Criminal Law Perspective in Indonesia - Anita Zulfiani; Nabila Alinka Wibowo; Tika Andarasni Parwitasari (Proceeding International Conference on Digital Education and Social Science, 2025)
The growing incidence of bullying in schools causes physical and psychological harm to children and demands examination from multiple perspectives. This study analyzes bullying in the school environment from a criminal law perspective, examining how it can be classified as a criminal offense and how criminal liability is imposed on children who engage in bullying. The research employs a normative juridical method, drawing on statutory and conceptual approaches. The findings show that bullying may fulfill the elements of various criminal offenses, including defamation, slander, assault, fighting, group assault, offenses against decency, hate speech, threats of violence, discriminatory acts, and physical, psychological, and social violence, as well as indecent acts. These offenses are regulated in the Criminal Code, Law No. 1 of 2023 on the Criminal Code, the Law on Electronic Information and Transactions, and the Child Protection Law. The forms of criminal liability for children who commit bullying include: (1) settlement through restorative justice -implemented via diversion - that ensures the restoration of victims’ rights and a deterrent effect on perpetrators, where the offense is punishable by imprisonment of less than seven years and is not a repeat offense; and (2) main penalty and ancillary penalty for children aged 14, as well as a sanction in the form of a measure for children under 14 who commit crimes with a threat of less than 7 years. This study implies that a deeper understanding of the criminal law dimensions of bullying can enhance awareness and encourage more effective prevention and intervention in schools.